The effect of carbon tax and optimal slope profiles on profitability and emissions of open pit mines. Issue 1 (2nd January 2023) - Agosti, Andrea; Utili, Stefano; Tasker, James; Zhang, Chao; Knights, Peter; Nehring, Micah; Zia, Shoaib
ABSTRACT: This paper investigates the financial and environmental consequences stemming from the introduction of a carbon levy applied to mining and processing activities. The novelty is twofold: (1) the effect of a carbon tax, proportional to the emissions produced by all relevant mining activities, is accounted for in the determination of the Ultimate Pit Limit (UPL), i.e. the environmental costs are not applied a posteriori to pit optimization but included concurrently to Net Present Value (NPV) maximization, allowing to investigate the relationship between carbon tax value versus NPV, amount of ore extracted and carbon emissions; (2) we use a new software, OptimalSlope, to automatically determine geotechnically optimal profiles for the mine pitwalls. The Marvin copper deposit (block model data publicly available from MineLib repository) was adopted as a case study. Several pit optimizations were performed based on four different values of carbon tax and adopting either traditional planar or non-linear optimal pitwalls. It emerges that the relationships between carbon tax value versus NPV, amount of ore extracted, and carbon emissions exhibited linearity in both cases of planar and optimal pitwall profiles. Moreover, the adoption of optimal profiles realizes gains up to 215 million AUD, without compromising the safety of the UPL.